Energy use and energy efficiency development in the German and Colombian textile industries (2010)
This paper analyses energy efficiency development in the German and Colombian textile industries as case studies, using three alternative indicators to measure energy efficiency performance. The study analyses energy efficiency in the textile industry at the ISIC three-digit level of aggregation for the years 1998 to 2005. Comparing the results of the three alternative indicators, the German and Colombian textile industries improved their energy efficiency performance during the sample period. The energy consumption of each textile manufacturing activity corresponded to its production level, indicating the direct relation between output and energy use. The results show considerable variation in energy efficiency between the German and Colombian textile industries. A second-stage application of the constant elasticity of substitution (CES) production function reveals that in the German textile industry, capital and energy price variables enhance the efficiency of the gross production–energy ratio, whereas in the Colombian textile industry, labour, materials, and plant capacity utilisation variables enhance the efficiency of the gross production–energy ratio. Moreover, in the German textile manufacturing activities, improvements in energy efficiency are achieved mainly through process changes encouraged by energy prices and as an investment strategy, whereas in the Colombian textile manufacturing activities, improvements in energy efficiency are achieved mainly by changes in the production processes, investments in R&D ,and application of new technologies. These results show the importance of technology, economies of scale, and energy efficiency-oriented policies and management strategies in improving energy efficiency within the textile industry.